2009
DOI: 10.1103/physrevb.79.245407
|View full text |Cite
|
Sign up to set email alerts
|

Atomic jumps during surface diffusion

Abstract: The characteristics of atomic displacements during surface diffusion of Cu on Cu͑111͒ are studied by means of molecular dynamics simulations. It is found that even at very low substrate temperatures, the majority of the jumps are correlated, i.e., the displacement directions are not randomly chosen but rather keep some sort of memory from the previous moves and are influenced by them. Long jumps, spanning several surface unit cells, are observed at all temperatures. From an analysis of their length probability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…energy dissipation via frictional coupling is likely to be responsible for the occurrence of the hopping motion. On the other hand with increasing thermal energy compared to the potential energy surface, more and more long jumps start to set in during jump diffusion [58][59][60][61] , which is evident from the experimental data, since the best fit Chudley-Elliott model gives an average jump length of 1.4 a gr . Note that a similar diffusive motion was observed for molecular hydrogen on graphite with jump diffusion and also a very low activation energy 33,50,62 .…”
Section: Resultsmentioning
confidence: 84%
“…energy dissipation via frictional coupling is likely to be responsible for the occurrence of the hopping motion. On the other hand with increasing thermal energy compared to the potential energy surface, more and more long jumps start to set in during jump diffusion [58][59][60][61] , which is evident from the experimental data, since the best fit Chudley-Elliott model gives an average jump length of 1.4 a gr . Note that a similar diffusive motion was observed for molecular hydrogen on graphite with jump diffusion and also a very low activation energy 33,50,62 .…”
Section: Resultsmentioning
confidence: 84%
“…Long hops of atoms or clusters have been reported in several previous studies using field ion microscope or STM [47][48][49][50][51]; some also show that short hops dominate at low temperatures but long hops dominate at high temperatures [51]. The behavior of long hops is an interesting phenomenon in surface diffusion.…”
Section: E Hopping Mechanism Of Single Si Atoms On the ( 3 7 × )-Pb mentioning
confidence: 83%
“…Since we intended to observe and compare diverse atomistic processes taking place at several temperatures and on different time scales, the same integration time step of 1 fs was used in all simulations. The atomic coordinates were stored at intervals of 40 fs to allow us to follow the atomic trajectories with sufficient precision [10]. These coordinates have been used to produce movies that graphically display all the different cluster motion events, facilitating their identification and description by simple inspection.…”
Section: Methodsmentioning
confidence: 99%
“…III D. For all types of events, a time threshold of 0.8 ps was established: all jumps or rotations resulting in shorter residence times at the new position were considered fluctuations and discarded. The choice of this value was initially motivated by our previous work on the diffusion of Cu monomers on Cu(111) [10], where we found that the fastest diffusion processes for single atoms took at least ≈0.4 ps. As it will be shown in Sec.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation